2015
DOI: 10.1364/ol.40.002091
|View full text |Cite
|
Sign up to set email alerts
|

Laser damage density measurement of optical components in the sub-picosecond regime

Abstract: A rasterscan procedure adapted to the sub-picosecond regime is set to determine laser-induced damage densities as function of fluences. Density measurement is carried out on dielectric high-reflective coatings operating at 1053 nm. Whereas laser-induced damage is usually considered deterministic in this regime, damage events occur on these structures for fluences significantly lower than their intrinsic damage threshold. Scanning electron microscope observations of these "under-threshold" damage sites evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…This was accomplished by adjustment of AOI to appropriately shift the coatings' transmission spectra in wavelength so that the 1064 nm or 1053 nm LIDT wavelengths were either within the central spectral zones or near the band edges of the BBHR bands. The tests at 1053 nm were performed by L. Lamaignere and M. Sozet of CEA-CESTA in France on the BBHR coating of Run 072 using the laser test facility called DERIC [23] with 675 fs pulses in 1-on-1 and 10-on-1 formats based on ISO 11254-1 [21] and ISO 11254-2 [24] protocols, respectively. For 1-on-1 and 10-on-1 tests, these LIDTs are 1.34 J/cm 2 and 1.15 J/cm 2 , respectively, in the central part of the BBHR band (with 0° AOI), and are 1.15 J/cm 2 and 0.8 J/cm 2 , respectively, near the edge of the BBHR band (with 40° AOI, Ppol).…”
Section: Subsequent Coating Runs Based On the Bbhr Designmentioning
confidence: 99%
“…This was accomplished by adjustment of AOI to appropriately shift the coatings' transmission spectra in wavelength so that the 1064 nm or 1053 nm LIDT wavelengths were either within the central spectral zones or near the band edges of the BBHR bands. The tests at 1053 nm were performed by L. Lamaignere and M. Sozet of CEA-CESTA in France on the BBHR coating of Run 072 using the laser test facility called DERIC [23] with 675 fs pulses in 1-on-1 and 10-on-1 formats based on ISO 11254-1 [21] and ISO 11254-2 [24] protocols, respectively. For 1-on-1 and 10-on-1 tests, these LIDTs are 1.34 J/cm 2 and 1.15 J/cm 2 , respectively, in the central part of the BBHR band (with 0° AOI), and are 1.15 J/cm 2 and 0.8 J/cm 2 , respectively, near the edge of the BBHR band (with 40° AOI, Ppol).…”
Section: Subsequent Coating Runs Based On the Bbhr Designmentioning
confidence: 99%
“…Overall, it has been demonstrated that the laser damage resistance of an optic in the subpicosecond regime is both limited by its intrinsic properties (linked to its electronic structure) [7,8] and by the presence of embedded defects induced by the manufacturing process [4,9]. The densities of such embedded defects can be as high as two hundreds of defects∕cm 2 , estimated from the measurement of damage densities during rasterscan tests [10]. The questions we wanted to answer in this Letter are: Once a damage site is initiated, what is its growth probability?…”
mentioning
confidence: 99%
“…On the other hand, for lower fluences, the incubation effect can lead to the formation of damage when a pristine site is irradiated with multiple pulses [3]. Rasterscan experiments have also been done on the mirror to reveal the presence of embedded defects such as nodules [10]. It can be suggested that the initial damage can have an impact on growth behavior.…”
mentioning
confidence: 99%
“…LIDT tests of the BBHR coating of Run 072 were performed by CEA-CESTA in France using the laser test facility called DERIC 19 with 675 fs pulses of 1053-nm center wavelength and a 1∕e focal spot diameter on the coating surface of 155 μm. These were 1-on-1 and 10-on-1 tests based on the ISO 21254-2 protocols, 20 and the laser PRR was 10 Hz.…”
Section: Lidt Tests Of the Bbhr Coating Of Run 072mentioning
confidence: 99%